2013
DOI: 10.9790/0837-0825357
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between employee performance, leadership styles and emotional intelligence in an organization

Abstract: The interest in great leaders keeps growing in modern occasions, as society and technology are becoming growing in more complexes. The ever altering organizational atmosphere needed leaders who are able to satisfy the challenges and demands of organizations functioning in competitive complex conditions, with world open for trade. This study looks into the relationship between worker performances, leadership styles and emotional intelligence within an organization. Information was collected, using three instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
3
1
0
Order By: Relevance
“…This current study revealed the paramount role of Job satisfaction as the mediator on the relationship between learning organization and Organizational commitment. This expanded the role of Job satisfaction as the mediator as found in other studies (Claudia, 2018;Fitriyana et al, 2016;Sakiru et al, 2018). The close and strong correlations between job satisfaction and organizational commitment had shown that these two concepts, while conceptually different, did share many similarities in the antecedents.…”
Section: Mediating Role Of Job Satisfactionsupporting
confidence: 74%
See 3 more Smart Citations
“…This current study revealed the paramount role of Job satisfaction as the mediator on the relationship between learning organization and Organizational commitment. This expanded the role of Job satisfaction as the mediator as found in other studies (Claudia, 2018;Fitriyana et al, 2016;Sakiru et al, 2018). The close and strong correlations between job satisfaction and organizational commitment had shown that these two concepts, while conceptually different, did share many similarities in the antecedents.…”
Section: Mediating Role Of Job Satisfactionsupporting
confidence: 74%
“…Along with other studies that had shown that job satisfaction acted as a mediator on the impacts of other crucial variables such as job engagement and leadership, this study reinforced the dire need for management to identify ways to boost the job satisfaction of lecturers (Li et al, 2017;Sakiru et al, 2018). Therefore, job satisfaction was paramount not only to enhance organizational commitment of lecturers, it could buffer the impact of learning organization as well.…”
Section: Mediating Role Of Job Satisfactionsupporting
confidence: 71%
See 2 more Smart Citations